Pandemic and Regional Disintegration: COVID-19 and the Dismantling of the South American Security Community - Frenkel, Alejandro; Dasso Martorell, Agostina (FLACSO - Sede Ecuador, 2021)
The article analyzes the development of a security community in South America and the impact that the coronavirus pandemic had on it. By using a constructivist methodology, the paper analyzes how the crisis of regionalism, the difficulty in defining common threats and the erosion of a collective identity hampered the maturation of the community. In this context, it is argued that the health crisis caused by COVID-19 gave rise to a securitization process that deepened the process of dismantling that community and was reflected in three indicators: 1) the proliferation of discourses that identify neighbors as a threat to safety and health; 2) a fortification of the borders; 3) an increase in the militarization of citizen security and other spheres of the public arena. It is concluded that this type of practice and discourse gives rise to a type of political community similar to an anarchic society, where states identify themselves as rivals rather than friends.